PERPINDAHAN PELANGGAN (CUSTOMER SWITCHING) DALAM PEMASARAN JASA: SEBUAH ANALISIS KONSEPTUAL - Alexander Joseph Ibnu Wibowo (Center for Economic Studies Universitas Katolik Parahyangan, 2013)
The main goals of this paper are: (i) to review the literatures on customer switching occurred in business services, (ii) to identify the antecedents of customer switching in service business, and (iii) to provide recommendations for managers to avoid or reduce customer migration. This paper is a conceptual study through a literature review on the various articles in leading marketing journals. This paper presents various opinions of the authors and a discussion about customer switching growing to date. This study shows that companies have to pay attention to keep their customers from their competitors. Several factors determining customer switching such as attitudes about switching, subjective norms, customer dissatisfaction, and perceived quality are analyzed. The study shows that companies will gain profit by retaining their customers.Keywords: Switching, Services Marketing, Loyalty, Profitability, Push-Pull-Mooring (PPM) Model